Strategi Komunikasi Humas PT KCI Dalam Program CSR Pojok Baca di Stasiun Jakarta Kota - Putriana, Muria; Sari, Wina Puspita; Sitorus, Putri Yohana; Kurnia, Salsabila; Candra, Ghina Salsabila; Paramita, Theresia Resa; Budiono, Riyaan; Fauzan, Nugraha Robby (Universitas Majalengka, 2024)
The aim of this research is to identify the public relations strategies of PT KAI in communicating the CSR program